Toward a Practical, Civic Piety: Mitt Romney, Barack Obama, and the Race for National Priest - Crosby, Richard Benjamin (Rhetoric & Public Affairs, 2015)
In 2008, two of the leading presidential candidates emerged from controversial, outsider religious groups—Mormonism and the black church tradition. Dogged by ongoing questions from the media, each candidate produced a high-profile public address. In this article, I argue that Mitt Romney’s “Faith in America” and Barack Obama’s “A More Perfect Union” craft competing visions for American civic piety. Drawing on recent literature in the area of practical piety, I read the speeches as evidence that civic piety may be more than a subordinating, pragmatic agreement between church and state. It may instead be read as a spiritually substantive space of cultural identity formation. I further conclude that the 2008 election reveals a contested piety in the midst of transition, and that this transition points in a relatively well-defined direction for American civil-religious culture.
https://katalog.adlr.link/Record/ai-55-aHR0cHM6Ly93d3cuanN0b3Iub3JnL3N0YWJsZS8xMC4xNDMyMS9yaGV0cHVibGFmZmEuMTguMi4wMzAx